Lower urinary tract transitional cell carcinoma in cats: Clinical findings, treatments, and outcomes in 118 cases. (13th November 2019) - Griffin, Maureen A.; Culp, William T. N.; Giuffrida, Michelle A.; Ellis, Peter; Tuohy, Joanne; Perry, James A.; Gedney, Allison; Lux, Cassie N.; Milovancev, Milan; Wallace, Mandy L.; Hash, Jonathan; Mathews, Kyle; et al.
Abstract: Background: Lower urinary tract transitional cell carcinoma (TCC) is an important but rarely described disease of cats. Objectives: To report the clinical characteristics, treatments, and outcomes in a cohort of cats with lower urinary tract TCC and to test identified variables for prognostic relevance. Animals: One‐hundred eighteen client‐owned cats with lower urinary tract carcinoma. Methods: Medical records were retrospectively reviewed to obtain information regarding clinical characteristics, treatments, and outcomes. Recorded variables were analyzed statistically. Results: Median age of affected cats was 15 years (range, 5.0‐20.8 years) and median duration of clinical signs was 30 days (range, 0‐730 days). The trigone was the most common tumor location (32/118; 27.1%) as assessed by ultrasound examination, cystoscopy, or both. Treatment was carried out in 73 of 118 (61.9%) cats. Metastatic disease was documented in 25 of 118 (21.2%) cats. Median progression‐free survival and survival time for all cats were 113 days (95% confidence interval [CI], 69‐153) and 155 days (95% CI, 110‐222), respectively. Survival increased significantly ( P < .001) when comparing cats across the ordered treatment groups: no treatment, treatment without partial cystectomy, and treatment with partial cystectomy. Partial cystectomy (hazard ratio [HR], 0.31; 95% CI, 0.17‐0.87) and treatment with nonsteroidal anti‐inflammatory drugs (HR, 0.55; 95% CI, 0.33‐0.93) were significantly associated with longer survival times. Conclusions and Clinical Importance: The results support treatment using partial cystectomy and NSAIDs in cats with TCC.